Metal complexes of dietary flavonoids: evaluation of radical scavenger properties and protective activity against oxidative stress in vivo - Kostyuk, V.A.; Potapovich, A.I.; Kostyuk, T.V.; Cherian, M.G. (Cellular and Molecular Biology, 2007)
Interaction of certain flavonoids with transition metals increases their water solubility and leads to the formation of flavonoid-metal complexes, which may act as superoxide dismutase mimics with high scavenger potencies toward superoxide. Effect of serum albumin on stability of flavonoid-metal complexes was studied and complex of rutin with iron (II) was found to be the most stable. The ability of flavonoid metal complexes to catalyze homolytic cleavage of hydrogen peroxide was also studied and rutin iron (II) complex was found to be relatively poor Fenton catalyst. The potential therapeutic benefits of this new antioxidant agent were studied using experimental model of pathological states associated with oxidative stress in vivo. Acute hepatic injury in MT-I/MT-II null transgenic mice induced by injections of thioacetamide was used for this purpose. It was found that pretreatment with rutin- iron complex protected against thioacetamide induced hepatotoxicity as observed by a significant reduction in the elevated levels of serum enzymes and partial normalization of GSH/GSSG ratio, glutathione peroxidase II and glutathione reductase activity in mice liver. The results demonstrate that flavonoid-metal complexes possess effective free radical scavenger ability and have potent therapeutic benefits for the treatment of oxidative stress-related diseases and dysfunction.